UJI EFEKTIVITAS ANTIDIABETES EKSTRAK ETANOL DAUN YAKON (Smallanthus sonchifolius.) PADA TIKUS JANTAN (Galur Wistar) YANG DIINDUKSI NICOTINAMIDE DAN STREPTOZOTOCIN - Anggun Syafitri; Hazimah Fitriyah Mardatilah; Nanda Kurniawan (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2026)
Diabetes mellitus is a chronic metabolic disease characterized by hyperglycemia due to impaired insulin secretion or action. The use of synthetic antidiabetic drugs has a variety of side effects, so the search for alternatives from natural ingredients is constantly being carried out. Yakon leaves (Smallanthus sonchifolius) are known to contain flavonoids such as quercetin which have antidiabetic activity through antioxidant mechanisms and inhibition of glucose-decomposing enzymes. To determine the effectiveness of yakon leaf ethanol extract (EEDY) in lowering blood glucose levels (KGD) in male rats of the Wistar strain induced by nicotinamide and streptozotocin, and to compare it with the positive control of glibenclamide. The experimental study used 25 mice divided into 5 groups: negative control (Na-CMC), positive control (glycenchalamide 0.45 mg/kgBB). and three treatment groups with EEDY doses of 100, 200, and 400 mg/kgBB. Induction of diabetes is carried out with streptozotocin and nicotinamide. KGD was measured before and after treatment and was performed on days 4, 8, 12, 16, 20, 24, and 28. The administration of EEDY showed a significant reduction in KGD (p<0.05) compared to negative controls. The dose of 400 mg/kgBB provides the greatest decreasing effect, approaching the effectiveness of glibenclamide. Statistical analysis showed that there was a significant difference between the negative control group and the treatment.